The effect of biofertilizer and different rate of chemical fertilizer on the growth of rice (Oryza sativa) MR 263 under glasshouse condition - Nasorudin, Amirul Syafiq (2015)
The biofertilizer or microbial inoculants can generally be defined as preparation containing live and efficient nitrogen fixing, phosphate solubilizing or cellulolytic microorganisms used for applying to seed, soil, or composting. The use of biofertilizer also lead to fertile soil, promote the growth of paddy, and environmental quality. Meanwhile, the use of many chemical fertilizers will lead to toxic effect on plant growth and caused environmental pollution. This experiment will determine the effect of biofertilizer (UPMB10 and GM118) and different rate of chemical fertilizer on the growth of paddy variety M263. It was conducted at Kompleks Ladang Bersepadu, Ladang 10, Universiti Putra Malaysia while the culturing of the bacteria was conducted at Agrotechnology Laboratory, Department of Agriculture Technology, Faculty of Agriculture, Universiti Putra Malaysia. The rice plants were grow under four treatments of biofertilizer (T1) – control, (T2) – UPMB10, (T3) – GM118 (T4) – GM118 + UPMB10. Each treatment also has the different ratio of chemical fertilizer (NPK). The treatment was applied at an early and middle stage of growth and the parameters collected at day 70 (maturation phase) were plant height, fresh and dry weight of plants and amount NPK in leaves tissue. Completely randomized design was used as the experimental design with four replicates. All data collected were subjected to ANOVA to determine the effect of biofertilizer on the growth of paddy and Tukey test were used for means separation. Result showed that the treatment containing combination biofertilizer and higher rate of fertilizer gives the highest result better than other treatments. From the data obtain in this study it showed that, the biofertilizer application on variety MR263 had significant difference between each treatment for plant height, chlorophyll contain, fresh weight, dry weight and NPK content in leaves tissue. The best result for this experiment is treatment (GM118 + UPMB10) with fertilizer 8 compared to other treatments. As conclusion the combination biofertilizer showed the best result better than treatment of using single biofertilizer and control.